MODERNIZATION OF INTEGRATED DAYAH EDUCATIONAL SYSTEM IN DARUL MUKHLISIN BURNIJIMET - Nur, Ismet (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
The existence of Dayah as an Islamic educational institution in Central Aceh District has a major role in the development of diversity in community. Step by step, the educational institution is developing, both in quality and quantity. Departing from this reality, this paper uses a phenomenological approach, examines the modernization of Darul Mukhlisin?s integrated Dayah educational system, which includes the Dayah education sub-systems. The modernization of the education system is characterized by changes in the aspects of objectives, Teungku and Santri Dayah, implementation of an integrated curriculum, the treasury of contemporary books, use of active strategies and varied methods, environmental changes, the application of test and non-test evaluation types, and so forth. Thus, the existence of Darul Mukhlisin was able to become a bastion of religious education in producing religious cadres and religious generations in Central Aceh.